Perbedaan Pandangan Masyarakat Terkakit Acara Tahlilan di Kabupaten Lombok - Suhadah Suhadah; Rudi Rudi; Edo Edo (Universitas Muhammadiyah Mataram, 2024)
This article discusses the views of the community regarding tahlilan activities for Muslims who have been stricken by the disaster of death. More specifically, this study aims to find out the various views of society for Muslims who have been stricken by the disaster of death. From this research it is known that tahlilan activities are a tradition of some Islamic societies that have been cultured in the local culture so that these activities have been passed down from generation to generation. However, the problem lies in the different perspectives of society regarding the law in carrying out the tahlilan tradition in Islam. Therefore the method used by researchers is a qualitative method where the data used is in the form of survey results with the aim of knowing how the community's perspective on the tahlilan tradition is.